DETEKSI DINI KUALITAS MINYAK GORENG DAN STUDI AWAL TINGKAT KEHALALANNYA MENGGUNAKAN POLARISASI ALAMI - Eva, Yulianti; Indriyani, Y; Husna, A; Putri, N Kharisma; Murni, Sri; Amitasari, Ria; Putranto, Ari Bawono; Sugito, Heri; Firdausi, K Sofjan (BERKALA FISIKA, 2014)
In this paper, we investigate natural light polarization for preliminary test of quality and authentication (halal) level of frying oil. Recently standard methods used are usually based on Indonesian National Standard (SNI), however all parameters are very difficult to be determined simultaneously. On the other hands even the test is time consumed, inexpensive, complicated and also preliminary treatments required, which is a major problem in era of rapid information need. One of an alternative solution is to use natural light polarization method. In the experiment, several vegetable frying oils and animal oils are used to be tested. The change of polarization angle is used to indicate the level of oil quality and its authentication. The result shows that higher polarization indicates lower oil quality relative to the others, which is in agreement to the previous study. This method is, not only, able to differentiate various edible vegetable oils, but also to distinguish edible oils and expired oils. More over, it has a prospect to indicate an authentication of oil that is a subject of a halal or not-halal case.This method is relative simply, not time consumed, conducted accurately without any previous treatments, and it provides a good prospect as a preliminary test for oil quality and its authentication. Keywords: Natural polarization, oil quality, halal or authentication level